(untitled) (Globalization and Business, 2023)
Since the dawn of the computer and internet era, many online users have exploded, and more people are using the Internet to spend their money online. Georgia is well-known and well-positioned as a regional gambling hotspot. Gambling is a strategically vital and financially lucrative industry for the country. The gambling business plays a crucial role in the Georgian economy by contributing to its budget revenues via income generated from licenses and spending of foreign tourists and increasing employment by hiring a steadily increased number of employees in the field. Gambling is a steadily growing industry with an increasing number of players raises several behavioral questions on why so many people decide to play online and the main factors that determine and affect their choices. Even though online gambling is a strategically important and financially attractive field for Georgia, it is, at the same time, a source of many social problems such as gambling addiction, the involvement of adults, and financial problems. Gamblers maintain behavioral habits by attempting to deny concerns and a false sense of control. As a result, gambling becomes the most important activity in a person's life. Its nature is so broad that it complicates the process and makes it difficult for gamblers to recover. Therefore, this case requires a thorough study from various perspectives. These aspects lack scientific studies of the local market or other related research papers that add novelty to the Georgian online gambling segment. This research examines several traditional approaches to gambling behavior, their proclivity for problem gambling, and the primary elements that influence it.